The effect of e-local tax return usage towards local tax compliance - Wibowo, Hari Tri (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2020)
The objectives of this study were to explore the factors that affected the usage of e-local tax return, user satisfaction and local tax compliance, such as subjective norms, output quality, self-efficacy, anxiety, perceived usefulness, perceived ease of use, and intention to use e-local tax return. The data collecting method was through a survey by spreading questionnaires to taxpayers who already use e-local tax return. The total of the respondent was 62 people and the data taken was managed by using SmartPLS3 software. The research results showed that subjective norm and output quality did not affect the perceived usefulness. However, self-efficacy and anxiety took effect on the perceived ease of use. Perceived ease of use took effect on perceived usefulness, intention to use e-local tax return, and user satisfaction. Perceived usefulness took an effect on user satisfaction, but it did not affect the intention to use e-local tax return. intention to use took an effect towards e-local tax return usage. Then e-local tax return usage took an effect on local tax compliance, but it did not affect user satisfaction. User satisfaction did not affect local tax compliance. These research results can be tools to plan a strategy for the Board of Finance and Asset Management of Yogyakarta City related to the implementation of e-local tax return in the future.